Aspects of the biology of the musselcracker, Sparodon Durbanensis, and the bronze bream, Pachymetopon grande, (Pisces : Sparidae), with notes on the Eastern Cape recreational rock-angling and spear fisheries - Clarke, John Ross (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1988)
The musselcracker, Soarodon durbanensis, and the bronze bream, Pachymetopon arande, are important components of rock-angling and spearfishing catches In the Eastern Cape. Aspects of their biology, including age and growth, reproduction, nursery areas and feeding, were Investigated to provide a basis for the rational exploitation of the resource. Both species are slow-growing and long-lived. Growth in S. durbanensls was described by the von Bertalanffy growth equation: Lt(mm) = 1021.2(1-eâ »Â°.Â°â ¹Â°Â°â ½t â »Â° .â ·Â°â ¹â ¾). The von Bertalanffy growth model did not describe the total data set in P. grande, but by excluding the zero and one year old fish the data were described by: Lt(mm) = 461.1(1-eâ »Â°.Â¹â µÂ³â ½t â ºÂ¹.â ¶â ´Â°â ¾). Detailed histological examination of gonadal development showed that S. durbanensis and P. grande are rudimentary hermaphrodites. Both species had restricted breeding seasons which coincided with peak exploitation. Results indicated that both species are group spawners with pelagic eggs. Size at 50% maturity in S. durbanensis and P. grande was determined at 350 and 300mm fork length, respectively, corresponding to ages of 4.5 and 5.5 years. Intertidal pools functioned as nursery areas for S. durbanensis during the first year, whereas subtidal waters were more important for larger juveniles. P. grande juveniles were commonly observed on subtidal weed beds to a depth of 10m. A size-related change in the diet of S. durbanensis was observed. The juveniles were omnivorous, feeding predominantly on gastropods, echinoids and chlorophytes. The adults fed on a variety of large, reef-associated invertebrates. P. grande were omnivorous, with macroalgae being the principal dietary component. This species appears to utilise the storage and extracellular carbohydrates of the macroalgae. Results showed that macroalgal degradation by gut endosymbionts and the utilisation of macroalgal epibionts does not appear to occur in this species. A detailed analysis of catch composition and catch per unit of effort In the Port Elizabeth rock-angling fishery and the Eastern Cape spearfishery emphasised the recreational importance of S. durbanensis and P. grande. The localised distribution, slow growth and late maturation in both species results in their being susceptible to over-exploitation in these size-selective fisheries. Current legislation protecting these fish is discussed in relation to the findings of this study and additional management measures are proposed.
Keywords: Sparidea -- South Africa; Sparodon; Durbanensis; Bream fishing